Pengaruh Paklobutrazol dan Ga3 Terhadap Pertumbuhan dan Pembungaan pada Tanaman Tomat (Solanum lycopersicum) - Nikolaus Widyasmara; Rochmatino Rochmatino; Lucky Prayoga (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2019)
Tomato is a horticultural commodity that has many benefits, it not only functions as a fruit vegetable but is also often used as a complement to spices, food coloring ingredients and fresh drinks because of its nutritional content. To increase tomato production, paklobutrazol is needed. Paklobutrazol has a function to inhibit the biosynthesis of gibberellins, so that the administration of these substances causes stunting elongation and stimulates flower induction. While GA3 serves to encourage the development of seeds, elongation of stems, encourage flowering and fruit development. This research was conducted with the aim of assessing the effect of Paklobutrazol and GA3 on growth and flowering on tomato plants and determine the concentration of Paklobutrazol and GA3 which are appropriate for the growth and flowering of tomato plants. This research was carried out experimentally using a completely randomized design (CRD) 2 factor factorial pattern. Each treatment combination was repeated 3 times so that there were 48 experimental units. The concentrations of paklobutrazol used were 0 ppm, 250 ppm, 500 ppm, and 750 ppm, while the concentration of GA3 used was 0 ppm, 50 ppm, 100 ppm and 150 ppm. The parameters observed in this study were plant height (cm), flowering time (days), and number of flowers (fruit). The data obtained were analyzed by Analysis of Variance with a confidence level of 95%, and continued with the Smallest Significant Difference test (LSD) at an error rate of 5%. The results showed that administration of paklobutrazol had an effect on inhibiting the height of tomato plants, and GA3 had an effect on accelerating flowering of tomato plants. Paklobutrazol with a concentration of 750 ppm is the best concentration to inhibit plant height, and GA3 with a concentration of 150 ppm is the best concentration to spur tomato flowering.